The role of Mycoplasma pneumoniae in dermatological diseases - Podraza, Zofia; Durmaj, Aneta; Papierzewska, Małgorzata; Czuwara, Joanna; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2024)
Mycoplasma pneumoniae is an atypical bacterium causing respiratory tract infections mainly in the pediatric population. As a superantigen, it dysregulates the immune system and promotes immunological reactions. Dermatological symptoms occur in approximately one-fourth of the patients infected with this bacterium. This review describes skin diseases occurring during Mycoplasma pneumoniae infection. Differences in the course of these diseases compared to their presentation associated with other etiological factors, are also discussed. Among the cutaneous manifestations of Mycoplasma pneumoniae infection, unspecific rashes and urticaria are the most common. This bacterium is also a frequent cause of erythema multiforme, Stevens-Johnson syndrome, Mycoplasma-induced rash and mucositis, and erythema nodosum. Less frequently toxic epidermal necrolysis, leukocytoclastic vasculitis, IgA vasculitis, subcorneal pustular dermatosis, Gianotti-Crosti syndrome, and Sweet syndrome are described. Familiarity with Mycoplasma-induced entities is important and can be useful in dermatological practice in determining the etiology and implementing appropriate treatment.